Investigation of Causes of Shock of Banking System of Lithuania (1994–1996) - Šadžius, Linas (Ekonomika, 2001)
Banking system, its stability and effective activity are important factors for each society especially that one, which is in the period of transition from planned to market economy. Commercial banks of Lithuania in the period of transformation economy, during big inflation and recession time, as in other post-communist countries of Central and Eastern Europe, didn’t avoid tearing up. By the end of 1995 in the Bank of Lithuania were registered 27 commercial banks but really were in business only 12 (44 per cent of total sum of commercial banks), when by the end of 1994 really had worked 22 (82 per cent). The peak of shock was in December of 1995 when moratorium was promulgated for two biggest commercial banks of Lithuania. Banking shocks directly affected approximately 30 per cent and indirectly almost 70 per cent Lithuania’s firms, almost 200 thousand population experienced bigger or smaller losses. The causes of financial shock generally can be divided into two categories: those induced by macroeconomic factors and those caused by poor microeconomic infrastructures. The two were interdependent. Inopportune adoption of some laws and their inefficiency was too one of main causes. Shocks of commercial banks has damaged development of financial system and economy, and for a time banks lost a confidence in Lithuania and abroad as well.